2023
DOI: 10.1126/science.adg9931
|View full text |Cite
|
Sign up to set email alerts
|

Air quality policy should quantify effects on disparities

Abstract: New tools can guide US policies to better target and reduce racial and socioeconomic disparities in air pollution exposure

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 13 publications
0
20
0
Order By: Relevance
“…For example, Mohai and Kweon suggest best practices for school-siting policies, based on a review of policies in seven states . Our results emphasize the importance of action, including reducing pollution in overburdened communities. , …”
Section: Resultsmentioning
confidence: 63%
“…For example, Mohai and Kweon suggest best practices for school-siting policies, based on a review of policies in seven states . Our results emphasize the importance of action, including reducing pollution in overburdened communities. , …”
Section: Resultsmentioning
confidence: 63%
“…Within the United States, it has been shown that census tracts with lower socioeconomic status are exposed to higher PM 2.5 concentrations, and that increased PM 2.5 is associated with increased age-specific mortality. 98 The adverse effects of air pollution related to health are not homogeneously distributed, and individuals residing within lower socioeconomic status areas face greater burdens of CMD as a consequence of increased exposure to air pollution. 5 Moreover, green space initiatives involving investments in parks and greenways may unintentionally result in "green gentrification, " defined as the influx of wealthier individuals to lower income neighborhoods in which green space initiatives are being implemented.…”
Section: Socioeconomic Disparities In Urban Provisioning Systemsmentioning
confidence: 99%
“…60,63,64 There are 2 hypotheses driving these disparities, either that the populations themselves are more susceptible due to chronic disadvantage or they have higher risks because of increased exposures. 65,66 Also, often, it is difficult to disentangle the effects of minority status from differences in SES.…”
Section: Race/ethnicity/nativitymentioning
confidence: 99%
“…[72][73][74][75] Conversely, the pollution reduction benefits are also likely to be unevenly distributed within a population and require additional knowledge on which subgroups may derive preferential benefit. 65…”
Section: Race/ethnicity/nativitymentioning
confidence: 99%